2008
DOI: 10.4314/eamj.v85i8.9655
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and oral health status of an elderly population in Nairobi

Abstract: Objective: to determine the nutrition and oral health status of elderly persons in Nairobi, Kenya. Design: a cross-sectional study. Setting: households in dagoretti division of Nairobi. Subjects: two hundred and eighty nine persons (29.8% males and 70.2% females) aged 45 years and above were assessed. Results: the level of malnutrition using the mid upper arm circumference was 18.8% while by body mass index was 11.4%. of the population assessed, 46.4% had normal nutritional status while 40.9% were overweight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
1
14
2
Order By: Relevance
“…BMI has been used as an independent indictor of malnutrition in many studies in Africa (6,9). These studies found a prevalence of undernutrition in older persons (BMI 18.5 kg=m 2 ) ranging between 9.5% and 36.1% in men and between 13.1% and 27.0% in women; our findings also fall within this range.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…BMI has been used as an independent indictor of malnutrition in many studies in Africa (6,9). These studies found a prevalence of undernutrition in older persons (BMI 18.5 kg=m 2 ) ranging between 9.5% and 36.1% in men and between 13.1% and 27.0% in women; our findings also fall within this range.…”
Section: Discussionsupporting
confidence: 80%
“…These studies found a prevalence of undernutrition in older persons (BMI 18.5 kg=m 2 ) ranging between 9.5% and 36.1% in men and between 13.1% and 27.0% in women; our findings also fall within this range. Similarly, gender differences in nutritional status are also found to be manifested in older persons in other countries (4,5,9,17). Thus, food insecurity is a problem in the Lake Victoria Basin (10,11,12).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other parameters that are used to determine the progress of obesity are an assessment of waist circumference, the ratio of waist to hip circumference, and the measurement of total body fat. There are also works in the literature, providing evidence for the existence of a relationship between the above-listed parameters of the degree of obesity qualification and indicators evaluating the progression of periodontal disease and oral hygiene [ 19 ].…”
mentioning
confidence: 99%
“…Most of the Kenyan surveys have targeted the adult population for measurement of dental caries [8,9]. But even those done in children targeted the urban population [10][11][12].…”
Section: Overall Susceptibility To Dental Cariesmentioning
confidence: 99%